Tracked Changes. Residual current operated circuit-breakers for household and similar use. Specific requirements for devices with screw-type terminals for external untreated aluminium conductors and with aluminium screw-type terminals for use with copper or with aluminium conductors Part 3-3, (8th August 2023) - British Standards Institution,
No abstract available